Citizens' perception of digital public services: A case study among Romanian citizens - Mirona Ana Maria Popescu; Andreea Barbu; Georgiana Moiceanu; Iustina-Cristina Costea-Marcu; Gheorghe Militaru; Petronela Cristina Simion (Administrative Sciences, 2024)
Digital transformation has become a topic of interest since public institutions digitalize their processes to improve efficiency, while citizens wish to solve their issues through online platforms. Even if this topic is a priority, the Digital Economy and Society Index reveals that digital public services from UE are under 30% development and implementation. This paper presents the current research made on digital public services and the perspective of Romanian citizens on the adoption of these platforms. The authors conduct bibliometric research to highlight the current progress and concerns. Furthermore, a quantitative analysis is made to determine the perception of Romanian citizens on digital public services and the factors that influence their decision to use them instead of traditional methods. According to the bibliometric analysis, 23 countries showed a raised interest for digital public services after 2020, which was a crucial moment that pushed digitalization among public institutions. Although Romanian citizens are aware of the benefits brought by digital public services, they encounter issues in terms of lack of information and technical support, knowledge, data security, and the complexity of these platforms. Therefore, the government should implement an integrated approach that considers cultural values as well as reliable and accessible digital solutions.
Keywords: 350; digital public services; e-government; digital platforms; citizen engagement; publicorganization